Pengaruh Penambahan Curcuma mangga dan Lama Penyimpanan terhadap Kerusakan Daging Ayam Kampung - Ilyasa, Mohammad; Pujimulyani, Dwiyati; Tamaroh , Siti (Jurnal Sain Peternakan Indonesia, 2023)
Chicken meat is a favoured animal ingredient, but its antimicrobial activity makes it perishable. Chicken meat can be stored frozen, but thawing takes a long time. Curcuma mangga Val. is antibacterial and has antioxidant activity that can extend the shelf life of an ingredient. The study aimed to determine the effect of adding C mangga pulp or filtrate on the damage of native chicken meat during storage. The treatments in the study controlled fresh chicken meat, chicken meat with the addition of C mangga pulp (DBT) and chicken meat with the addition of C mangga filtrate (DFT) with a storage time of 0, 3, 6, and 9 days at 4°C. The testing parameters were water content, protein content, total plate count, salmonella contamination, colour and pH. Free-range chicken meat with the addition of C mangga filtrate stored for three days showed a total plate number according to SNI, damaging salmonella contamination, and lightness and pH were not significantly different from the control. The best result is the length of storage of native chicken meat with the addition of C mangga filtrate for three days.